National Social Health Insurance Program in Bara District of Nepal: A Systematic Review Paper - Kafle, Bishnu Raj (Journal of Development Review, 2025)
The assessment of the SHI program's current state in Nepal's Bara District is the main objective of this study, which also looks at the program's obstacles to enrolment. Additionally, it summarizes the potential for increasing SHI availability and offers suggestions for improving SHI practice and policy. Using keywords that delved into understanding occupation, income, and awareness of participation in SHI, the publications were gathered from academic sites such as PubMed, Scopus, and Google Scholar. The research and survey show that those with low incomes and those in informal employment avoid registering in the SHI program because of cultural norms, ignorance, and financial difficulties. Administrative obstacles and a general lack of suitable health facilities have also been identified as cross-cutting problems that impede SHI. The study's last sections, the conclusions, include recommendations for public awareness campaigns, low-income earner subsidies, the creation of appropriate institutions, and easier-to-follow protocols. The above-mentioned actions aim to advance the idea of UHC(Universal Health Coverage) in Nepal by assisting SHI enrolment and utilization in Bara District and possibly resolving some of the issues.